Assisted Self‐Assembly to Target Heterometallic Mn‐Nd and Mn‐Sm SMMs: Synthesis and Magnetic Characterisation of [Mn7Ln3(O)4(OH)4(mdea)3(piv)9(NO3)3] (Ln=Nd, Sm, Eu, Gd). Issue 61 (13th October 2021) - Kaemmerer, Hagen; Mereacre, Valeriu; Ako, Ayuk M.; Mameri, Samir; Anson, Christopher E.; Clérac, Rodolphe; Powell, Annie K.
Abstract: In an assisted self‐assembly approach starting from the [Mn6 O2 (piv)10 (4‐Me‐py)2 (pivH)2 ] cluster a family of Mn−Ln compounds (Ln=Pr−Yb) was synthesised. The reaction of [Mn6 O2 (piv)10 (4‐Me‐py)2 (pivH)2 ] (1 ) with N ‐methyldiethanolamine (mdeaH2 ) and Ln(NO3 )3  ⋅ 6H2 O in MeCN generally yields two main structure types: for Ln=Tb−Yb a previously reported Mn5 Ln4 motif is obtained, whereas for Ln=Pr−Eu a series of Mn7 Ln3 clusters is obtained. Within this series the Gd III analogue represents a special case because it shows both structural types as well as a third Mn2 Ln2 inverse butterfly motif. Variation in reaction conditions allows access to different structure types across the whole series. This prompts further studies into the reaction mechanism of this cluster assisted self‐assembly approach. For the Mn7 Ln3 analogues reported here variable‐temperature magnetic susceptibility measurements suggest that antiferromagnetic interactions between the spin carriers are dominant. Compounds incorporating Ln=Nd III (2 ), Sm III (3 ) and Gd III (5 ) display SMM behaviour. The slow relaxation of the magnetisation for these compounds was confirmed by ac measurements above 1.8 K. Abstract : Assisted self‐assembly by using a preformed [Mn6 O2 (piv)10 (4‐Me‐py)2 (pivH)2 ] (1 ) (pivH=pivalic acid) cluster leads to 3 different outcomes of the reaction with Ln(NO3 )3  ⋅  x H2 O (Ln=Pr−Ho and Y): Mn7 Ln3 and in some cases the inverse butterfly Mn2 Ln2 for Ln=Pr−Eu, Mn5 Ln4 for Ln=Tb‐Ho and in the special case of Gd all three possibilities can form. Whilst the magnetic properties for the Mn5 Ln4 systems show the expected known SMM properties, for Mn7 Ln3 two new examples of Nd‐ and Sm‐containing SMMs have been discovered.